Pengaruh Budaya Organisasi, Pelatihan Kerja, dan Lingkungan Kerja terhadap Kinerja Pegawai Kantor Kementrian Agama Kota Kediri - Nia Putri Amelia; Indah Yuni Astuti; Angga Permana Mahaputra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the influence of organizational culture, job training, and work environment on the performance of employees at the Office of the Ministry of Religious Affairs of Kediri City. The research employed a quantitative approach using a saturated sampling technique involving 69 employees. Data analysis was conducted using statistical tests with the assistance of SPSS version 26. The results showed that partially, organizational culture, job training, and work environment had a significant effect on employee performance. This was proven by the calculated t-values of each variable, which were greater than the t-table values, and significance values less than 0.05. Simultaneously, the three variables also had a significant effect on employee performance, indicated by the calculated F-value being greater than the F-table value and the significance value being less than 0.05. Therefore, the alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected.